PENGARUH KEPUASAN KERJA TERHADAP KOMITMEN KARYAWAN DI UPTD PUSKESMAS SUKARAJA KABUPATEN SUKABUMI - Setia Nesda, Ajeng; Dety Mulyanti (MANABIS: Jurnal Manajemen dan Bisnis, 2023)
In achieving organizational goals, it is necessary to properly manage the human resources in it. The Puskesmas is an organization where human resources or employees are called to have a major influence in achieving the goals of the Puskesmas. Job satisfaction is one of the factors that can affect employee commitment to the organization. In fact, there are many phenomena and problems that indicate that something is not right that is felt by the employees of the UPTD Puskesmas Sukaraja. Therefore, we will conduct research on the effect of job satisfaction on employee commitment at the UPTD Puskesmas Sukaraja. This research is a descriptive quantitative study using a simple linear regression statistical test with the independent variable being job satisfaction and the dependent variable being employee commitment. The results of the sample calculation using the slovin formula obtained the number of samples as many as 40 of the total population of 68 people. The sampling technique was taken using random sampling technique. The results showed that there was a relationship between job satisfaction and employee commitment and job satisfaction had a significant effect on employee commitment at the UPTD Puskesmas Sukaraja